Compendium of success stories of farmers practising natural farming in Himachal Pradesh - Mandla, Ishita; Sharma, Subhash (Indian Farming, 2023)
India is an agrarian economy and ranks second in the world in terms of agricultural production. To double the income of farmers by 2022, government has realigned its interventions from a production-centric approach to farmers’ income-centric initiatives. The present day agricultural activities rely on costly inputs like chemical fertilizers and quality seeds for improving yield; however, this comes at the cost of economic viability and environmental degradation in the long run. Himachal Pradesh government is determined to increase farmers' income and their long-term welfare. They also launched the 'Natural Farming Happy Farmer' scheme in the year 2018. In its very first budget, the government has implemented 'Subhash Palekar Natural Farming' method under this scheme toreduce the use of chemicals in farming. Launched with a financial provision of 25 crores, the scheme has sought to reduce the cost of cultivation and enhance income for the comprehensive welfare and prosperity of farmers and gardeners.